Reasons for Culling in Relation to Longevity and Lifetime Efficiency of Landrace and Large White Sows in a Nucleus Breeding Farm in the Philippines - O. Bondoc; J. Isubol (Tropical Animal Science Journal, 2022)
Information on the reasons for sow removal is limited and often unreported for nucleus breeding farms. This study analyzed the distribution of culling type (planned vs. unplanned) and culling reasons in relation to longevity – parity at culling (PAC) and productive herd life (PHL), and lifetime efficiency – lifetime pigs born alive (LPBA) and total pigs weaned (TPW) using data recorded from 2017 to 2019 by a local nucleus breeding farm. The study revealed a considerable amount of unplanned removal (84.1%) compared to planned culls, which is due to old age (11.4%) and poor farrowing performance (4.6%). The most common reasons for unplanned sow removal were reproductive failures (26.2%) and health disorders (23.4%), followed by physical defects (15.3%), leg/foot problems (10.8%), and mortality (8.5%). A high proportion (22.1%) of sows was culled at their first parity. The proportion of culled sows decreased up to parity 4, especially for unplanned sow removals due to reproductive failures, leg/foot problems, and mortality. Unplanned culling corresponded to lower PAC (3.8), PHL (459 days), LPBA (14.1 pigs/year), and TPW (12.4 pigs/year). Average PAC and PHL were significantly higher (p<0.05) for Large White sows (PAC= 5.2; PHL= 696 days) than Landrace sows (PAC= 4.6; PHL= 588 days). However, the LPBA and TPW were not significantly different between breeds. Information about sow removal could be used to develop management strategies to avoid unplanned culling in purebred sows and extend their productive life.